Optical performance of welding curtains and existing standards. Issue 7 (29th June 2021) - Dain, Stephen J.; Sliney, David H.; Naumov, Andreas
Abstract: Welding curtains and screens are intended to protect workers, other than the welder, from the effects of optical radiation generated by the welding process. The national and international standards for welding screens and curtains have different requirements. The aim is to compare the protection requirements of examples of welding curtain material and to assess compliance with the international and national standards. Spectral transmittance values (ultraviolet, visible, and infrared) of 21 samples were obtained from the records of an ISO/IES 17025 accredited test laboratory and performance/compliance was assessed according to each of the standards. In the ultraviolet, 10 samples passed and seven failed all standards. In the visible/infrared region, four samples passed and 10 failed all standards. Four samples passed the U.S. and international standards but failed the Australian/New Zealand standard in the blue-light transmittance requirement. One sample failed both the U.S. and Australian/New Zealand standards but the result for the international standard was borderline, one sample passed ISO but failed the blue-light requirements, and one failed ISO but passed the blue-light requirements. The derivations of the various requirements are not well documented. The Australia/New Zealand standard is significantly more stringent in the ultraviolet and blue-light regions. A review of the optical radiation hazards and revision of the standards are indicated. It is possible that curtains, other than those tested, that comply with the international standard might transmit hazardous levels of blue light and, conversely, adequate ultraviolet and blue-light protection is available with curtains that do not comply with the international standard.